Sangam: From Romance to Realism - Robina Kausar (بازیافت)
Ahsan Frooqi's novel "Singham" belongs to those novels which were created by inspiration of division of 1947. This division of India and Pakistan forced every mind to think about what is the relationship of the people who live in India. The character of 'Muslim' in India is permanent forever, he considers everything to the world and he forgets even to God in the love of world at last he accesses toward reality through Roman.